Intracellular expression of MICA in activated CD4 T lymphocytes and protection from NK cell-mediated MICA-dependent cytotoxicity. - Molinero, Luciana Lorena (2006)
MICA is a stress-regulated molecule recognized by the NK cell-activating receptor NKG2D. Previously, we demonstrated that MICA is induced on activated T cells but regulation by mitogenic cytokines and its biological consequences remain unexplored. Here, we show that IL-2, IL-4, and IL-15 but not TNF-alpha or IFN-alpha induced MICA expression in T lymphocytes present in peripheral blood mononuclear cells (PBMCs), as assessed by Western blot. IL-2 effect involved Jak3/STAT5, p38 MAPK, p70(56) kinase, Lck/fyn kinases, and NF-kappaB. MICA expression was also observed in Th1 and Th2 cells. However, surface expression was not detected. T lymphocytes present in PBMCs and isolated CD4+ T lymphocytes stimulated with phorbol-12-myristate-13-acetate and ionomycin also induced MICA expression as assessed by Western blot, but only low levels were expressed at the cell surface. Activated but not resting CD4+ T lymphocytes were lysed by IL-15- or IL-2-stimulated NK cells, and susceptibility was increased when HLA class I molecules were blocked. Also, cytokine-stimulated NK cells produced more IFN-gamma after culture with activated CD4+ T lymphocytes. However, the participation of MICA in these responses, if any, was marginal. Confocal microscopy revealed that MICA is retained mostly inside activated CD4+ T cells. Our results suggest that low surface expression of MICA on activated CD4+ T lymphocytes might be a safeguard mechanism to protect them from NK cells in an inflammatory, virus-infected, or tumor microenvironment, where NK and activated CD4+ T cells are recruited.